Role of NS1 antibodies in the pathogenesis of acute secondary dengue infection - Deshni Jayathilaka; Laksiri Gomes; Chandima Jeewandara; Geethal. S. Bandara Jayarathna; Dhanushka Herath; Pathum Asela Perera; Samitha Fernando; Ananda Wijewickrama; Clare S. Hardman; Graham S. Ogg; Gathsaurie Neelika Malavige (Nature Communications, 2018)
The antibody response during infection with dengue virus is a key component involved in the pathogenesis during secondary infection. Here the authors show antibodies targeting NS1 and the epitopes targeted can be associated with disease severity during human infection.